Effects of collaborative innovation activities, collaborative innovation capability, and knowledge sharing on public sector's innovation performance - Dinna Ayu Widyasari; Yasmine Nasution (President University, 2022)
Agriculture sector in Indonesia is very important as they are responsible for the overall growth and productivity of the country’s economy and in maintaining human life, considering that food is a basic need and human right. Therefore, public sector must find an effective way to achieve higher agricultural productivity, which can be done by collaborating with other firms. Built on knowledge management theory and collaborative innovation theory, this study aims to examine whether there is an effect of collaborative innovation activity (CIA), knowledge sharing (KS), and collaborative innovation capability (CIC) on the innovation performance (IP) either directly, or through moderation with each other to study the mechanism of collaborative innovation process at the Indonesian Agency for Agricultural Research and Development. Regarding the objective and research model, we empirically validate the survey data for 48 Indonesian Agency for Agricultural Research and Development under the Ministry of Agriculture with SEM PLS method. This study prove that joining in collaborative innovation activities is the key to improve their innovation performance, and knowledge sharing plays a mediating role in the relationships between collaborative innovation activities and firm’s innovation performance. This study also prove that collaborative innovation capability is not the only factor that determines the success of a company’s innovation performance, since the result shows that CIC has no impact on the relationship between CIA to IP, and KS to IP.